The challenges, coping mechanisms, and recovery from the initial waves of the COVID-19 pandemic among academic radiographers. (October 2022) - Knapp, K.M.; Venner, S.; McNulty, J.P.; Rainford, L.A.
Abstract: Introduction: The COVID-19 pandemic arrived in Europe in March 2020 and created major challenges across healthcare provision and for healthcare education programmes as well as having a major impact on society. Within the profession of Radiography changes in medical imaging, radiotherapy, and teaching practices have been reported along with the negative impact on radiographers and students. The aim of this study was to investigate key challenges relating to academic practice during the COIVD-19 pandemic; how radiography academics have coped and to identify recommendations for further support required to facilitate recovery of the academic faculty as the pandemic ebbs. Methods: A survey was circulated using SurveyMonkey™ via personal, national and international networks, including the European Federation of Radiographer Societies (EFRS), to reach as many academic radiographers as possible. Open questions relating to the challenges of providing radiography education during the COVID-19 pandemic and the and coping strategies used were included. Thematic analysis was conducted using NVivo (QSR International, MA). Results: 533 academic radiographers responded to the whole survey from 43 different countries, with 340 responses relating to challenges and 327 for coping strategies. The main themes for the challenges were clinical practice, communication with colleagues, lack of face to face, managing change, students (support), and staff support. The coping strategy themes were communication with colleagues, physical exercise, self-care and wellbeing. Conclusion: These data demonstrate a multitude of challenges for academic radiographers and the pressure they worked under during the first year of the COVID-19 pandemic was clear. However, the majority employed healthy coping strategies to help them deal with the pressure, uncertainty and trauma of the situation. Implications for practice: COVID-19 had a significant impact on academic radiographers and while many reported good strategies for coping, the level of pressure is unsustainable. This study highlights the need to support academic radiographers to ensure a sustainable workforce.